Management and safety of a medical mission: occupational hazards of volunteering. Issue 2 (17th February 2016) - Tan, Aidan; Fong, Yuke Tien; Ho, Sweet Far; Tay, Boon Keng; Chua, Yeow Leng
ABSTRACT: Medical aid missions involve travel to conflict or danger zones, posing safety risks in addition to the usual occupational risks arising from daily medical work. The note reports on a volunteer mission, using personal reports, anecdotal experiences, and the formal annual report to undertake an assessment similar to worksite assessments for hazards and control measures. Hazards were found to be prevalent, including physical noise and heat, infectious exposure from patients and local vectors, poor water sanitation, and psychosocial stress from unfamiliar environments and large patient numbers with limited means. Implementable preventative measures include increasing awareness with appropriate protective equipment usage and safety guidelines. Mission planning and management should also involve occupational health input.